Reduced Glutathione and Cysteine Hydrochloride on Sperm Motility and Velocity Parameters of Poor Crossbred Bull Semen - Perumal, P.; Selvaraju, S.; Barik, A. K.; Mohanty, D. N.; Das, S.; Mishra, P. C.; Veeraselvam, M. (International Journal of Bio-resource and Stress Management, 2012)
The effect of reduced glutathione (5 mM) and cysteine hydrochloride (5 mM) on sperm velocity and motility parameters of good (3) and poor (3) freezable Jersey crossbred bull semen was studied. The post-thawed sperm velocity and motility parameters were assessed by computer assisted sperm analyzer (CASA) at different hours of incubation. The forward progressive and total motility showed significant (p<0.05) difference in glutathione treated group as compared to cysteine treated and control group in both freezer. In both freezers, the forward progressive and total motility was not decreased significantly up to 2 h of incubation but thereafter there was a highly significant decrease. A gradual non-significant decline in all the velocity parameters in good freezable semen samples were observed for the 4 periods of incubation and in poor freezable semen, the reduction in the velocity parameters was not significant up to 2 h of incubation, but thereafter, the decrease was significant. The velocity parameters of sperm revealed that the glutathione treated group was non-significantly higher than cysteine treated and control group in both good and poor freezable bulls except the addition of glutathione significantly improved VCL (curvilinear velocity) and ALH (amplitude of lateral head displacement) of the post-thawed spermatozoa at 4 h of incubation. Further, the addition of cysteine and glutathione has non-significantly improved the other velocity parameters in both the freezer. Thus, the reduced glutathione has improved the post-thawed sperm functional parameters such as motility and velocity in good and maintained in poor freezable semen.